Limited Liability and the Risk-Incentive Relationship - Jörg Budde; Matthias Kräkel (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2008)
Several empirical findings have challenged the traditional view on the trade-off between risk and incentives. By combining risk aversion and limited liability in a standard principal-agent model the empirical puzzle on the positive relationship between risk and incentives can be explained. Increasing risk leads to a less informative performance signal. Under limited liability, the principal may optimally react by increasing the weight on the signal and, hence, choosing higher-powered incentives.
urn:nbn:de:bvb:19-epub-13320-7
Keywords: D82; D86; 330; moral hazard; limited liability; risk-incentive relationship